Optimization of Water Utilization Through the Application of Hydropande Technology to Meet Clean Water and Agricultural Needs in Timuhun Village, Banjarangkan District, Klungkung Regency - I Komang Ery Kusnada; I Ketut Sudiarta; I Gusti Agung Putu Eryani; Yohanes Parlindungan Situmeang; Dewa Nyoman Sudita; Nengah Muliarta (Agriwar Journal, 2024)
Timuhun Village, located in Banjarangkan District, Klungkung Regency, covers an area of 375 hectares with a population of 3,334 in 2021. Approximately 86.67% of the total land is utilized for agriculture, including rice fields, gardens, and dry fields, with a total agricultural area of 325 hectares. This village plays a significant role in food production, especially rice, supported by the irrigation system from Subak Timuhun, which utilizes the Manik Tirta Spring. However, challenges in water management arise due to the higher elevation of agricultural land compared to water sources, leading to difficulties in meeting the demands for clean water and irrigation. The Appropriate Technology of Hidropande is introduced as a solution to lift water from lower sources. This study aims to develop an integrated water management model by analyzing the residual water volume from the Manik Tirta Spring, determining the irrigation requirements for the paddy-cassava-paddy cropping pattern, and planning optimal water management strategies. Utilizing CROPWAT 8.0 software, this research estimates the water needs of crops based on various climatic and soil parameters. The results indicate that the highest irrigation water requirement reaches 41 mm/decade in December, while the lowest demand of 6.8 mm/decade occurs during the maturation phase of the plants. With calculations showing surplus residual water of 1.97 liters/second, the potential discharge from the Manik Tirta Spring can be maximized to support irrigation and meet clean water needs, alongside plans for developing a more efficient Hidropande pump. This study provides valuable insights into sustainable water management in Timuhun Village.